The proteomic effects of ketone bodies: implications for proteostasis and brain proteinopathies - García-Velázquez, Lizbeth; Massieu, Lourdes (Frontiers in Molecular Neuroscience, 2023)
A growing body of evidence supports the beneficial effects of the ketone bodies (KBs), acetoacetate and β-hydroxybutyrate (BHB) on diverse physiological processes and diseases. Hence, KBs have been suggested as therapeutic tools for neurodegenerative diseases. KBs are an alternative fuel during fasting and starvation as they can be converted to Ac-CoA to produce ATP. A ketogenic diet (KD), enriched in fats and low in carbohydrates, induces KB production in the liver and favors their use in the brain. BHB is the most abundant KB in the circulation; in addition to its role as energy fuel, it exerts many actions that impact the set of proteins in the cell and tissue. BHB can covalently bind to proteins in lysine residues as a new post-translational modification (PTM) named -hydroxybutyrylation (Kbhb). Kbhb has been identified in many proteins where Kbhb sites can be critical for binding to other proteins or cofactors. Kbhb is mostly found in proteins involved in chromatin structure, DNA repair, regulation of spliceosome, transcription, and oxidative phosphorylation. Histones are the most studied family of proteins with this PTM, and H3K9bhb is the best studied histone mark. Their target genes are mainly related to cell metabolism, chromatin remodeling and the control of circadian rhythms. The role of Kbhb on physiological processes is poorly known, but it might link KB metabolism to cell signaling and genome regulation. BHB also impacts the proteome by influencing proteostasis. This KB can modulate the Unfolded Protein Response (UPR) and autophagy, two processes involved in the maintenance of protein homeostasis through the clearance of accumulated unfolded and damaged proteins. BHB can support proteostasis and regulate the UPR to promote metabolism adaptation in the liver and prevent cell damage in the brain. Also, BHB stimulates autophagy aiding to the degradation of accumulated proteins. Protein aggregation is common to proteinopathies like Alzheimer’s (AD) and Parkinson’s (PD) diseases, where the KD and BHB treatment have shown favorable effects. In the present review, the current literature supporting the effects of KBs on proteome conformation and proteostasis is discussed, as well as its possible impact on AD and PD.